Plastic vs. policy : a plastic pollution policy analysis in the Arctic - Louise Meta-Maria Wittwer 1994- (2024)
Plastic pollution is a global problem that can be found everywhere on Earth, even in remote places like the Arctic. Negative impacts of plastic pollution include threats to life, health, and fitness of a multitude of species and the ecosystems they live in. Effects on humans include impacts on health as well as socio-economic and cultural impacts on individuals and whole communities. For this reason, different strategies aim at mitigating these impacts by minimizing the amount of plastic entering the environment or reducing plastic in the environment through clean-up strategies. Policies are a popular tool to address the plastic pollution issue on an international, national, or local level. This study aims to conduct an international plastic policy analysis comparing the Arctic nations Greenland, Iceland, the Faroe Islands, and Norway in relation to their policies. As plastic pollution easily spreads from country to country it is important that countries cooperate on the issue and harmonize regulations. In order to do so policies are reviewed, and semi-structured stakeholder interviews are conducted for a comprehensive study. The results of the study indicate different tendencies to represent the problem of plastic pollution throughout the decades. Differences could be observed between the four chosen Arctic countries. This research’s scientific contribution includes providing an overview of existing policies in the Arctic and highlighting gaps in existing policies. Lastly, this study is crucial for community development and the implementation of future plastic pollution policies. Plastmengun er hnattrænt vandamál sem er til staðar alls staðar á jörðinni, jafnvel á fjarlægum stöðum eins og Norðurskautinu. Neikvæð áhrif plastmengunar fela í sér ógn við lífríkið, heilsu, og hæfni fjölmargra tegunda og vistkerfa sem þær lifa í. Áhrif á menn fela í sér áhrif á heilsu sem og félags-hagræn og menningarleg áhrif á einstaklinga og heil samfélög. Af þessari ástæðu miða ólíkar áætlanir að því að milda þessi áhrif með ...